TEACHERS’ ROLE IN HANDLING MULTICULTURAL’ CLASSROOM; OVERVIEW ON TEACHING STRATEGIES AND MEDIA - yasyir fahmi mubaraq; Yulieda Hermaniar; Tri Winindyasari Palupi (IAIN Syekh Nurjati Cirebon, 2019)
Multicultural classroom deals with variety of students’ background in terms of mother tongue, etnicity, and culture. In the teaching and learning process, the variety is considered in deciding the appropriate strategies in media. Therefore, the discussion on teaching strategies as well as the media used applied in the classroom is considered important. This research is aimed at finding out those aspects in the perspective of descriptive qualitative study. The subject of the study are English teachers who teach at vocational school with various majors. the data obtained through observation are analized descriptively using Cresswell’s stages; transcribing, coding and classifying, interpreting, and drawing the conclusion. The result of this research shows that teachers still take significant role in classroom. Teachers’ strategies and media are also decided based on students’ characteristics from different kind of school.